HUBUNGAN FREKWENSI PEMBERIAN ELECTRO CONVULSIVE THERAPY (ECT) TERHADAP TINGKAT KECEMASAN PASIEN DENGAN SKIZOFRENIA DI RS JIWA PROVINSI BALI - M. Intan Juwita Dewi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Abstract. People with severe mental disorders estimated to rise in developing countries with increasingly severe crisis levels, One of them in Indonesia. The prevalence of most mental disorders are schizophrenia. Schizophrenia itself is a form of psychosis which are common everywhere, is a persistent and serious brain disease that lead to psychotic behavior, concrete thinking, and difficulty in information processing, interpersonal relationships, and solve problems. One of the therapy given as a treatment is Electro convulsive Therapy (ECT). ECT is an action that uses electrical currents that cause seizures. ECT is carried out in practice as much as 6-12 times for clients with affective disorders and the most common 3 times a week, Any patients who would receive ECT and often, they will experience different levels of anxiety associated with the psychological suffered by patients with schizophrenia. This study aims to find an relationship between the frequency of ECT in anxiety levels of patients with schizophrenia. The design of this study using cross sectional design. The population in this study were all patients with schizophrenia who received ECT in the Rumah Sakit Jiwa Provinsi Bali, where the entire population sampled as many as 15 people. The results are presented in table form and narrative. From the characteristics of the respondents found that most respondents sex men, educated past primary school. The results showed that most samples are performed with a frequency of 1-4 ECT by the number of 6 people (40%), respondents who experienced mild anxiety levels as much as 6 people (40%). Spearman's-Rho test p value = 0.003 was found and a correlation coefficient of -0710 which shows a negative value, it is stated there is a correlation or relationship between the frequency is inversely proportional to the provision of electro convulsive therapy (ECT) on the level of anxiety, so it can be concluded if patients with schizophrenia have frequency of ECT therapy are the higher the level of anxiety experienced by these patients would be lower.